Kontribusi Padi Sawah dan Aneka Ternak Terhadap Income On Farm: Kasus Kelompok Diversifikasi Usahatani di Gowa, Sulawesi Selatan - Paly, Muhammad Basir (Universitas Islam Negeri Alauddin Makassar, 2025)
Diversifying rice cultivation with livestock farming in paddy fields has the potential as an alternative effort to increase Income On Farm (IOF) for rural farming households. This research aims to analyze the contribution of rice cultivation and livestock farming to IOF. The study was conducted from April to July 2024 in Gowa Regency, involving three farmer groups that consistently implemented diversification programs for 15 consecutive years. A total of 60 sampled farmer group members were observed and interviewed. The measured variables were: income from rice cultivation; income from cattle farming; income from goat farming; income from chicken farming; and income from duck farming. To determine the contribution of each independent variable (Xi) to the dependent variable, IOF (Y), multiple linear regression analysis was conducted. The coefficients in the regression model can be interpreted as measures of contribution. The analysis process included classical assumption tests, feasibility and determination tests, simultaneous influence tests, and regression coefficient tests. The results showed that income from rice cultivation (X1), income from cattle farming (X2), income from chicken farming (X4), and income from duck farming (X5) had a positive and significant contribution to IOF, while income from goat farming (X3) was not significant. The paddy field ecosystem, besides serving as an energy and material source for living organisms, also functions as a physiological environment for livestock. The implications of these findings are that diversification has the potential as an alternative to increase IOF. This diversification model needs to be preferred and pursued by rice farming households and other stakeholders.